Protagonisti socialne geografije - Gosar, Anton (Geografski vestnik, 2021)
Social geography, which puts people and group interest at the forefront when dealing with the cultural landscape, has received a lot of internal criticism, but within the former Institute of Geography of the University of Ljubljana, led by Vladimir Klemenčič, it researched and recorded successes. Between 1970 and 2000,13 conferences with international participation were organised in Slovenia, Slovene geographers reportedat 93 conferences abroad, 16 associates lectured/researched at foreign universities for a longer period of time,25 student excursions and 44 guest lectures were registered. At the same time, during this period, geographers published 324 articles in foreign professional journals and monographs and established close contacts with 50 colleagues, mainly from Germany, Austria, Italy, France, United Kingdom and North America (United States and Canada). Social geography has proved itself in the promotion of Slovene science internationally as Slovenia became a sovereign nation-state in 1991. With a mix of social-, ethnic- and political-geographical research that favoured research in border and marginal areas, it has achieved a special status in the international professional community. Often, in particular in East/Central Europe, it has been called »The Slovenian School of Social Geography«. Despite of the closing of the Institute of Geography of the University of Ljubljanain 2002 the leading institution of socio-geographical research, socio-geographical thought still lives on in many partial research projects, which, in addition, include contemporary methodological approaches.
Keywords: 1970-2000; družbena geografija; geographical theory; history of geography; Inštitut za geografijo Univerze v Ljubljani; Slovenia; Slovenija; social geography; socialna geografija